Novi viri na internetu in njihova taksonomija - Kalčič, Dunja (Knjižnica, 2004)
The article describes new resources on the Internet and their taxonomy. The revised standard ISBD(CR) for continuing resources is presented, together with changes and differences in the bibliographic description of serials versus integrating resources. The main features of the ISSN-manual revision, standard and format are described, as well as the possibility of using the ISSN number as a resource identifier and as a persistent namespace identifier in the frame of a URN.
Keywords: mednarodni standardi; bibliografski opis; ISBD(CR); ISBD(S); serijske publikacije; kontinuirani viri; integrirni viri